Metastatic neuroendocrine tumor of small cell type in a kidney transplant recipient - Kamil, A. Mohd; Draman, Che Rosle; Seman, Mohd Ramli; R, Kalavathy; Mubarak, M. Y. (Saudi Center for Organ Transplantation, 2016)
Malignancy is a significant long-term complication of successful renal transplantation. Not only the rate is higher but also cases are highly aggressive. We report a case of metastatic, small cell, neuroendocrine tumor in a postrenal transplant patient with progressive left inguinal nodes and right lumbar swellings. He had a remarkably elevated serum lactate dehydrogenase levels with multiple metastatic masses in the left inguinal, left iliac fossa, and right lower abdominal wall on abdominal computed tomography scan. Excisional biopsy of a left inguinal node revealed extensive infiltration with malignant cells in it. Immunohistochemistry staining was positive for synaptophysin, prostatic specific antigen, and CD56. While the primary small cell carcinoma of genitourinary organs is rare, the case illustrates the highly aggressive nature of the disease in a kidney transplant recipient.